Rheological and foaming behaviors of long-chain branched polyamide 6 with controlled branch length. (14th May 2021) - Xu, Menglong; Lu, Jiawei; Zhao, Jinchuan; Wei, Linfeng; Liu, Tao; Zhao, Ling; Park, Chul B.
Abstract: A series of long-chain branched polyamide 6 samples (LCB PA6s) with well-defined branch length were successfully fabricated via reactive extrusion by tuning various linear PA6s as reactive materials. Their structure-property relationships were systematically investigated. The GPC-rheology method was performed to demonstrate the existence of LCB topological structure and quantitatively determine the relative branch length for three LCB PA6s. Rheological characterization showed that an increase in branch length resulted in the increased zero-shear viscosity and storage modulus at low frequency, reduced loss factor and high strain hardening coefficient under elongational flow, i.e., the enhanced elastic response and melt strength of PA6s. Finally, the melt foamability of the LCB PA6s were verified by batch foaming experiments with supercritical CO2 as the blowing agent. The LCB-Mb 4.5 with the longest branch length and highest melt strength appeared the biggest expansion ratio of 18.2 and broadest foaming window of 70 °C, which was expected to be in production on a large scale through continuous extrusion foaming process. Graphical abstract: Image 1 Highlights: LCB PA6s with well-fined branch length were first fabricated via reactive extrusion. The relative branch length was quantitatively determined using the GPC-rheology method. The rheological properties were greatly improved with increasing branch length. The LCB-Mb 4.5 sample exhibited the biggest expansion ratio and the broadest foaming window.